Pengelolaan Perhutanan Sosial Skema Hutan Nagari di Halaban, Lareh Sago Halaban, Kabupaten Limapuluh Kota - Ivo Ardyusri; Rozidateno Putri Hanida; Ria Ariany (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2026)
This research employed qualitative methods with a descriptive approach. Data were collected through interviews, observation, and documentation. Informants were selected using purposive sampling, while data validity was verified through source triangulation. The theoretical framework used is Ansell and Gash's collaborative governance, which encompasses four main variables: initial conditions, institutional design, facilitative leadership, and collaborative processes. The results indicate that social forestry management in Halaban reflects the principles of collaborative governance, although implementation has not been fully optimal. Initial conditions characterized by information imbalance and a history of conflict influence governance dynamics. Facilitative leadership from the nagari government and the Warsi Community Empowerment Community (KKI) plays a significant role in encouraging multi-stakeholder involvement. The institutional design through the establishment of the LPHN (National Forestry Development Agency) has been formally established, but administrative capacity and organizational independence still need to be strengthened. The collaboration process takes place through face-to-face dialogue and outreach, but this has not been done routinely, resulting in a lack of shared understanding. Nevertheless, various interim results, such as the establishment of the KUPS (National Forestry Unit), the drafting of Articles of Association (AD/ART), and the strengthening of area boundaries, indicate positive developments in social forestry governance. Overall, social forestry governance in Halaban has moved toward collaborative management, but still requires strengthening institutional capacity and consistent collaboration processes to achieve effective and sustainable management.